Transformational leadership and future work readiness among Chinese vocational college students: AI literacy and career self-regulation as dual mediators - Zehui, Ma; Tianyang, Zhang; Jiayuan, Jiang; Li, Wang (Frontiers in Education, 2025)
Amid accelerating digital transformation, students in vocational colleges face increasing uncertainty about their future career prospects. Grounded in the Cognitive Appraisal Theory (CAT) and Social Cognitive Career Theory (SCCT), this study proposed and tested a dual-path mediation model in which transformational leadership (TL) in educational settings influenced students’ future work readiness (FWR) through two mechanisms: AI literacy and career self-regulation (career control and decision-making difficulties) factors. The structural equation modeling and bootstrapped mediation analyses using data from 697 Chinese vocational college students revealed that TL indirectly enhanced career optimism and reduced future work anxiety through these mediators. Taken together, the findings are consistent with a full-mediation account: indirect effects were significant, and the direct links from TL to CO and to FWA attenuated to non-significance once the mediators were included. The findings positioned AI literacy as a critical cognitive bridge linking educational leadership to vocational psychological outcomes, and extended theoretical models of future work readiness and psychological adaptation to digitally evolving educational contexts.